Dental caries and periodontal disease (prevention and control methods) - San Juan, Sofrionio P. (The Journal of the Philippine Dental Association)
There is a compelling need to apply preventive programs in both private and community practice in dentistry. This is to maintain improvements in oral health in developed and industrialized countries, and to stem increases in oral diseases in underserved and developing ones. At the outset, the terms prevention and control must be understood. The former in considered to mean a procedure or course of action that prevents the onset of disease, whereas the latter, implies reversing or stabilizing disease conditions. To be more precise, prevention will refer to the pre-pathologic or pre-clinical stage encompassing the promotive and specific protection levels-primary prevention stage. On the other hand, control will encompass early diagnosis and prompt treatment, disability limitation and rehabilitation levels-termed also collectively, as pathologic, clinical and final stages, or secondary and tertiary prevention. Community-based programs are usually structured to compliment therapeutic interventions of oral diseases, as well as prevention. In this area, and towards the next millenium, preventive and control programs are given high priorities in order to minimize the need for curative, restorative and therapeutic management of oral diseases.